2021
DOI: 10.3390/nano11113058
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Rheological and Mechanical Properties of Isotropic and Anisotropic PP/rPET/GnP Nanocomposite Samples

Abstract: The effect of graphene nanoplatelets (GnPs) on the morphology, rheological, and mechanical properties of isotropic and anisotropic polypropylene (PP)/recycled polyethylene terephthalate (rPET)-based nanocomposite are reported. All the samples were prepared by melt mixing. PP/rPET and PP/rPET/GnP isotropic sheets were prepared by compression molding, whereas the anisotropic fibers were spun using a drawing module of a capillary viscometer. The results obtained showed that the viscosity of the blend is reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…The decrease of viscosity of polymer melt containing additives is reported before especially for fibers when oriented along the flow direction as well as for nano additives. 25 A few authors have reported in the past that the oriented short fibers in the polymer melt lead to reduction of the viscosity during processing. Nishitani and Kitano 26 observed decrease in viscosity of polyamide by addition of 1% of carbon nanofiber at all shear rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of viscosity of polymer melt containing additives is reported before especially for fibers when oriented along the flow direction as well as for nano additives. 25 A few authors have reported in the past that the oriented short fibers in the polymer melt lead to reduction of the viscosity during processing. Nishitani and Kitano 26 observed decrease in viscosity of polyamide by addition of 1% of carbon nanofiber at all shear rates.…”
Section: Resultsmentioning
confidence: 99%
“…Vaxman et al 28 conclude that the orientation of fiber in the direction of flow leads to decrease in melt viscosity. Francesco et al 29 reported that the melt viscosity measured by capillary rheometer in PP-rPET blend decreased by addition of 2% nanoparticle. In the present case, it is contented that the addition of R-PET above the critical concentration leads to nano-fiber formation of the dispersed phase and hence reduction in melt viscosity of the blend.…”
Section: Resultsmentioning
confidence: 99%
“…The main materials used in this work are as follows: [23]: average diameter between 1 and 2 µm; an average thickness lower than 2 nm; and a specific surface area of about 750 m 2 /g.…”
Section: Materials and Preparationmentioning
confidence: 99%
“…The drawing ratio, DR, of the fibers was computed, following the methodology detailed in a prior study [23], using the following formula:…”
Section: Characterizationmentioning
confidence: 99%
“…GNPs consist of two-dimensional graphite layers, and modern preparation methods can ensure thicknesses that range from one to several atoms [ 1 , 2 , 3 ]. Consequently, they possess very interesting electrical [ 7 , 8 , 9 , 10 , 11 , 12 ], mechanical [ 12 , 13 , 14 ] and rheological [ 15 , 16 , 17 ] properties. The incorporation of such carbonaceous fillers in a polymer matrix leads to some degree of electrical conductivity, with the resulting system exhibiting a percolation-type of behaviour [ 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%